Temporal variability of quasi-linear pitch-angle diffusion - Watt, Clare E. J.; Allison, Hayley J.; Bentley, Sarah N.; Thompson, Rhys L.; Rae, I. Jonathan; Allanson, Oliver; Meredith, Nigel P.; Ross, Johnathan P. J.; Glauert, Sarah A.; Horne, Richard B.; Zhang, Shuai; Murphy, Kyle R.; et al. (Frontiers in Astronomy and Space Sciences, 2022)
Kinetic wave-particle interactions in Earth's outer radiation belt energize and scatter high-energy electrons, playing an important role in the dynamic variation of the extent and intensity of the outer belt. It is possible to model the effects of wave-particle interactions across long length and time scales using quasilinear theory, leading to a Fokker-Planck equation to describe the effects of the waves on the high energy electrons. This powerful theory renders the efficacy of the wave-particle interaction in a diffusion coefficient that varies with energy or momentum and pitch angle. In this article we determine how the Fokker-Planck equation responds to the temporal variation of the quasilinear diffusion coefficient in the case of pitch-angle diffusion due to plasmaspheric hiss. Guided by in-situ observations of how hiss wave activity and local number density change in time, we use stochastic parameterisation to describe the temporal evolution of hiss diffusion coefficients in ensemble numerical experiments. These experiments are informed by observations from three different example locations in near-Earth space, and a comparison of the results indicates that local differences in the distribution of diffusion coefficients can result in material differences to the ensemble solutions. We demonstrate that ensemble solutions of the Fokker-Planck equation depend both upon the timescale of variability (varied between minutes and hours), and the shape of the distribution of diffusion coefficients. The uncertainty in the ensemble results increases for longer timescales of variability, and when the average diffusion coefficient at that location is high. We discuss time and length scales of wave-particle interactions relative to the drift velocity of high-energy electrons and confirm that arithmetic drift-averaging is can be appropriate in some cases. In other cases, further parameterisation is required to reduce uncertainty in the solution. We demonstrate that in some locations, rare but large values of the diffusion coefficient occur during periods of relatively low number density. Ensemble solutions are sensitive to the presence of these rare values, supporting the need for accurate cold plasma density models in radiation belt descriptions.